2022
DOI: 10.22460/infinity.v11i2.p367-380
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Students’ Mathematics Performance at Higher Education in Riau Province During the Covid-19 Pandemic

Abstract: This study aims to determine the factors influencing the students' mathematics performance in higher education in Riau Province. The research population was all students in higher education in Riau Province majoring in mathematics. The samples of this research were some students in higher education majoring in mathematics education which were taken randomly with a proportional random sampling approach. The instrument in this research was a questionnaire developed and validated by experts and distributed to mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
2
0
2
Order By: Relevance
“…Penilaian sumatif memberikan gambaran tentang sejauh mana siswa telah mencapai tujuan pembelajaran yang ditetapkan untuk periode waktu tertentu. Ini memberikan informasi penting tentang kesiapan siswa untuk melanjutkan ke tahap pembelajaran berikutnya (Izquierdo et al, 2024;Nofriyandi & Andrian, 2022). Hasil dari penilaian sumatif dapat memberikan wawasan kepada guru dan administrasi sekolah tentang efektivitas program dan metode pengajaran.…”
Section: Pendahuluanunclassified
“…Penilaian sumatif memberikan gambaran tentang sejauh mana siswa telah mencapai tujuan pembelajaran yang ditetapkan untuk periode waktu tertentu. Ini memberikan informasi penting tentang kesiapan siswa untuk melanjutkan ke tahap pembelajaran berikutnya (Izquierdo et al, 2024;Nofriyandi & Andrian, 2022). Hasil dari penilaian sumatif dapat memberikan wawasan kepada guru dan administrasi sekolah tentang efektivitas program dan metode pengajaran.…”
Section: Pendahuluanunclassified
“…Guru yang aktif dan memiliki kemampuan penggunaan teknologi dapat melakukan aktivitas pembelajaran bervariasi dapat meningkatkan minat, motivasi dan hasil belajar peserta didik. Kemampuan pendidik dalam menggunakan media pembelajaran interaktif memberikan kontribusi yang maksimal terhadap aktivitas pembelajaran yang mana awalnya peserta didik tidak menyukai pembelajaran matematika menjadi senang dan ingin terus belajar matematika (Bechter & Swierczek, 2017;Maclinton & Andrian, 2022;Nofriyandi & Andrian, 2022;Surya & Andriana Putri, 2017).…”
Section: Pendahuluanunclassified
“…Implementation of online learning has been carried out in various places in learning mathematics. Studies regarding the implementation of online learning in mathematics learning were carried out by several researchers, including (Aini, 2021;Azhari & Fajri, 2022;Fadila et al, 2021;Kusumaningrum & Wijayanto, 2020;Nofriyandi & Andrian, 2022;Restian, 2020;Simanjuntak et al, 2021;Suripah & Susanti, 2022;Sutriyani, 2020;Syarifuddin et al, 2021). In the learning process at several teaching and education faculties, online learning uses various applications (Aini, 2021;Manik, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Vice.com noted that a survey of 3,353 students who took part in online learning conducted by the UGM Center for Innovation and Academic Studies during the COVID-19 pandemic found that 66.9% of the research subject students showed a good category in understanding lecture material, and 33.1% of students in bad category (Azhari & Fajri, 2022;Nofriyandi & Andrian, 2022;Restian, 2020;Suripah & Susanti, 2022). This shows that students are not fully ready to take part in the online learning process, lecturer resources are not ready to manage distance learning, distance learning policies are not yet supported by an appropriate curriculum, facilities and infrastructure are not sufficiently supported, and internet networks are inadequate in some areas/ region.…”
Section: Introductionmentioning
confidence: 99%